Interferon Beta-1a versus Glatiramer Acetate: Changes of Innate Immunity in a Group of Women with Multiple Sclerosis - Peterka, Marek; Valis, Martin; Soucek, Ondrej; Krejsek, Jan; Sobisek, Lukáš; Sejkorova, Ilona; Klimova, Blanka; Stourac, Pavel; Pavelek, Zbysek; Novotny, Michal (European neurology, 2023)
INTRODUCTION: Multiple sclerosis (MS) is a chronic inflammatory autoimmune demyelinating disease that secondarily leads to axonal loss and associated brain atrophy. Disease-modifying drugs (DMDs) have previously been studied for their ability to affect specific immunity. This study investigates the effect of interferon beta-1a (INF) and glatiramer acetate (GA) administration on changes in innate immunity cell populations. METHODS: Sixty Caucasian female patients with relapsing-remitting MS undergo blood sample testing for 15 blood parameters at baseline, 1 month, 3 months, and 6 months after treatment by GA or IFN (started as their first-line DMD). RESULTS: A statistically significant difference in the change after 6 months was found in the parameter monocytes (relative count) in the group of patients treated with IFN. The median increase was 27.8%. Changes in many of the other 15 parameters studied were 10-20%. CONCLUSION: Innate immunity has long been neglected in MS immunopathology. The findings suggest that IFN treatment may modulate the immune response in MS by affecting monocyte function and may provide insight into the mechanisms of action of IFN in MS.
Keywords: Multiple sclerosis; přirozená imunita; Multiple Sclerosis; Interferon-beta; Glatiramer Acetate; relabující-remitující roztroušená skleróza; Multiple Sclerosis, Relapsing-Remitting; Immunity, Innate; Innate immunity; lidé; interferon beta; interferon beta 1a; ženské pohlaví; Glatiramer acetate; Humans; Monocytes; Peptides; Interferon beta-1a; peptidy; glatiramer acetát; Female; roztroušená skleróza